2011
DOI: 10.1109/jmems.2011.2159103
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Quality Factor From a Nonlinear Frequency Response With Jump Discontinuities

Abstract: The convenient half-power bandwidth formula used for measurement of quality factor Q does not apply for nonlinear systems that have jump discontinuities in their frequency responses, since one of the half-power amplitudes is not observable. This paper shows alternatives to the half-power formula that do apply to such nonlinear systems, while preserving all of the convenience of the method. Their practical use is illustrated by experimental Q measurements for a microelectromechanical systems scanning mirror.[20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…The fitted curves highlights a very good agreement between the model and experimental results. Compared to [6,7], Fig. 3 confirms that the fitting procedure requires very few experimental measurements around the maximal amplitude.…”
Section: A Experimental Setupmentioning
confidence: 59%
See 1 more Smart Citation
“…The fitted curves highlights a very good agreement between the model and experimental results. Compared to [6,7], Fig. 3 confirms that the fitting procedure requires very few experimental measurements around the maximal amplitude.…”
Section: A Experimental Setupmentioning
confidence: 59%
“…A recent study has demonstrated Q-factor estimation from a nonlinear frequency response [6], via precise measurements at low amplitudes (hence at low SNR) and the knowledge of the maximal amplitude on the frequency response, both of them difficult to measure in practice. Another study has demonstrated the efficiency of nonlinear least-squares fitting for parameter estimation of piezoelectric MEMS resonators from a nonlinear frequency response with jump discontinuities obtained through optical measurements [7].…”
Section: Introductionmentioning
confidence: 99%
“…where From the results in [96], if the forcing function F 0 is sinusoidal at the resonant frequency ω n , we can arrive at an estimate for the amplitude at resonance…”
Section: B12 Static Responsementioning
confidence: 99%
“…Recently, several works have focused on the characterization of MEMS resonators through their nonlinear (large-displacement) frequency response [17]- [20]. For SDOF systems, some of these studies have even achieved nonlinear characterization via least-squares fitting procedures [19], [20].…”
Section: Introductionmentioning
confidence: 99%